Liberal Violence and the Racial Borders of the European Union. Issue 6 (3rd September 2020) - Isakjee, Arshad; Davies, Thom; Obradović‐Wochnik, Jelena; Augustová, Karolína
Abstract: This paper examines how racial violence underpins the European Union's border regime. Drawing on two case studies, in northern France and the Balkans, we explore how border violence manifests in divergent ways: from the direct physical violence which is routine in Croatia, to more subtle forms of violence evident in the governance of migrants and refugees living informally in Calais, closer to Europe's geopolitical centre. The use of violence against people on the move sits uncomfortably with the liberal, post‐racial self‐image of the European Union. Drawing upon the work of postcolonial scholars and theories of violence, we argue that the various violent technologies used by EU states against migrants embodies the inherent logics of liberal governance, whilst also reproducing liberalism's tendency to overlook its racial limitations. By interrogating how and why border violence manifests we draw critical attention to the racialised ideologies within which it is predicated. This paper characterises the EU border regime as a form of "liberal violence" that seeks to elide both its violent nature and its racial underpinnings.